Orientação espacial em exoesqueletos de membros inferiores utilizando filtros Markovianos espaciais - Albuquerque, Patricia Raiana (Universidade Federal de São Carlos, 2021)
Studies of methodologies to obtain data on movements of the human body that involve losses of functional motor capacities due to neurological diseases, have aroused the inte- rest of several researchers to assist in the analysis of human movements. Among several methodologies, those involving the use of inerable sensors have become viable due to the low cost in relation to the systems optical reference. As a result of the use of inerable sensors, it is necessary to establish strategies that outsmart the sensitivity to inherent disturbances and errors these devices.In previous studies of this research group, angular estimates were made in the sagittal plane. In this work, the complementary fusion of the inerable sensors established by a Markovian system will be used to find the most suita- ble sensor every instant in conjunction with a Kalman filter to compensate for gyroscope deviation errors , but in three-dimensional space for absolute angles.In this context, a spa- tial orientation estimation system was developed in exoskeletons that minimized errors compared to a system optical reference. The results obtained in the work allowed com- pliance with the proposed requirements of the Markovian system to be validated based on a system optical reference.
Spatial orientation in lower limb exoskeletons using spatial Markovian filters
Keywords: Filtro de Kalman; Reabilitação robótica; Saltos Markovianos; Sensores Inerciais; Exoesqueleto de membros inferiores; Kalman filter; Robotic rehabilitation; Markovian jumps; Inertial sensors; Lower limb exoskeleton; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS